2019
DOI: 10.1002/anr3.12031
|View full text |Cite
|
Sign up to set email alerts
|

The use of high‐flow nasal oxygen during airway management in a child with epidermolysis bullosa dystrophica and a difficult airway

Abstract: Summary The role of high‐flow nasal oxygen in paediatric anaesthesia has been emerging in recent years. However, literature regarding its benefits in paediatric difficult airway management is limited. In this case report, we describe the use of high‐flow nasal oxygen during airway management of a child with a difficult airway due to epidermolysis bullosa dystrophica in whom the use of a facemask would have been potentially harmful. Deep sedation was achieved with propofol and remifentanil while maintaining spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…12,13 Recently, a case report described the use of high-flow nasal cannula oxygenation without complications in a pediatric patient with dystrophic epidermolysis bullosa, enabling avoidance of bag-mask ventilation and an unhurried approach to a difficult and fragile airway. 14 Our case series describes similar facilitation of airway management using THRIVE in adults. While airflow models have predicted higher shear stress in the nasal cavity and larynx from high oxygen flow rates compared to normal breathing, the clinical significance of this remains unclear.…”
Section: Discussionmentioning
confidence: 81%
“…12,13 Recently, a case report described the use of high-flow nasal cannula oxygenation without complications in a pediatric patient with dystrophic epidermolysis bullosa, enabling avoidance of bag-mask ventilation and an unhurried approach to a difficult and fragile airway. 14 Our case series describes similar facilitation of airway management using THRIVE in adults. While airflow models have predicted higher shear stress in the nasal cavity and larynx from high oxygen flow rates compared to normal breathing, the clinical significance of this remains unclear.…”
Section: Discussionmentioning
confidence: 81%
“…Silicone-based tape should be applied to the areas where the mask will contact the face. NgLY et al suggested using high flow oxygen as a preferable method instead of a face mask in children with difficult airways since it does not harm the mucosa and the skin [8].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Transnasal Humidified Rapid-Insufflation Ventilatory Exchange (THRIVE) may be used for preoxygenation and apneic oxygenation. 58 This technique employs use of high-flow nasal oxygen cannula placed over petrolatum gauze, reducing the risk of facial trauma from mask ventilation and prolonging the safe apneic time during difficult intubation. 58,59 Careful fiber-optic intubation with a well-lubricated, small endotracheal tube (size 5.0-or 6.0-mm internal diameter) is the recommended technique for airway management and carries the least risk of trauma to the airway.…”
Section: Airway Managementmentioning
confidence: 99%
“…58 This technique employs use of high-flow nasal oxygen cannula placed over petrolatum gauze, reducing the risk of facial trauma from mask ventilation and prolonging the safe apneic time during difficult intubation. 58,59 Careful fiber-optic intubation with a well-lubricated, small endotracheal tube (size 5.0-or 6.0-mm internal diameter) is the recommended technique for airway management and carries the least risk of trauma to the airway. 2,40,51 Oral airways and other intubating guides should be avoided due to the risk of shear force trauma.…”
Section: Airway Managementmentioning
confidence: 99%